Host Lipid Bodies as Platforms for Intracellular Survival of Protozoan Parasites - Toledo, Daniel A. M.; D’Avila, Heloísa; Melo, Rossana C. N. (Frontiers in Immunology, 2016)
Pathogens induce several changes in the host cell signaling and trafficking mechanisms in order to evade and manipulate the immune response. One prominent pathogen-mediated change is the formation of lipid-rich organelles, termed lipid bodies or lipid droplets, in the host cell cytoplasm. Protozoan parasites, which contribute expressively to the burden of infectious diseases worldwide, are able to induce lipid body genesis in non-immune and immune cells, mainly macrophages, key players in the initial resistance to the infection. Under host-parasite interaction, lipid bodies not only accumulate in the host cytoplasm but also relocate around and move into parasitophorous vacuoles. There is increasing evidence that protozoan parasites may target host-derived lipid bodies either for gaining nutrients or for escaping the host immune response. Newly formed, parasite-induced lipid bodies may serve as lipid sources for parasite growth and also produce inflammatory mediators that potentially act in the host immune response deactivation. In this mini review, we summarize current knowledge on the formation and role of host lipid bodies as sites exploited by intracellular protozoan parasites as a strategy to maintain their own survival.